2021
DOI: 10.3389/fpsyg.2021.695989
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Variables, Fear of COVID-19, Anxiety, and Depression: Prevalence, Relationships and Explanatory Model in the General Population of Seven Latin American Countries

Abstract: The COVID-19 pandemic has gravely impacted Latin America. A model was tested that evaluated the contribution of socio-demographic factors and fear of COVID-19 on anxiety and depression in samples of residents in seven Latin American countries (Argentina, Ecuador, Mexico, Paraguay, Uruguay, Colombia, and El Salvador). A total of 4,881 individuals, selected by convenience sampling, participated in the study. Moderate and severe levels of depressive symptoms and anxiety were identified, as well as a moderate aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 114 publications
1
21
0
Order By: Relevance
“…For this reason, the use of hypnotics could be considered a surrogate marker of the hypoestrogenism typical of menopause, a factor associated with a higher risk of presenting COVID-19. However, during the pandemic, studies have shown an increase in insomnia, anxiety disorders, and depressive symptoms related to the incertitude of life [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the use of hypnotics could be considered a surrogate marker of the hypoestrogenism typical of menopause, a factor associated with a higher risk of presenting COVID-19. However, during the pandemic, studies have shown an increase in insomnia, anxiety disorders, and depressive symptoms related to the incertitude of life [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Married workers tend to perceive more fear of infection and threat of job security during the pandemic, and be more worried about the poor working environment compared with unmarried workers. This could be explained by the fact that married workers not only care about themselves, but there is also a greater sense of responsibility and concern for the well-being of their family members, especially the children and aging parents [ 51 ]. In addition, the possible project shutdown caused by the COVID-19 pandemic may have made them more worried about job stability and job prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals from different demographic backgrounds may perceive various stressors during this pandemic in different ways. For the COVID-induced stressors, female workers have been found to report higher levels of fear of becoming infected, anxiety, and depression during the pandemic [ 50 , 51 , 52 ]. Elder people reported their greater worries about the severity of getting COVID-19 than the younger [ 53 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rodas et al [ 24 ] administered the CES-D to a sample of 663 participants in Ecuador during the early stages of the pandemic (March to June) and, although prevalence scores for depression were not reported, the sample average was 19.6 (SD = 11.05), which is above the suggested cut-off score of 18 for the detection of depression. Furthermore, Tusev et al [ 22 ] and Caycho-Rodriguez et al [ 21 ] both found higher levels of significant depression (25% and 25.9% respectively) and anxiety (31.8% and 25.4% respectively) in large online samples.…”
Section: Discussionmentioning
confidence: 99%
“…Paz et al [ 20 ], early in the pandemic, found 20.9% of people with suspected of confirmed COVID-19 had moderate to severe levels of depression, and 22.5% with moderate to severe anxiety symptoms. Caycho-Rodriguez et al [ 21 ] found similar levels of clinically significant depression and anxiety (25.9% and 25.4% respectively) using the same instruments in an online survey of 790 participants in the community. Tusev et al [ 22 ] found 25% reported clinically significant depression and 31.8% significant anxiety in an online survey using the 21 item depression, anxiety and stress scale (DASS-21).…”
Section: Introductionmentioning
confidence: 90%